FATP4 deletion in liver cells induces elevation of extracellular lipids via metabolic channeling towards triglycerides and lipolysis - Li, Huili; Seeßle, Jessica; Staffer, Simone; Tuma-Kellner, Sabine; Poschet, Gernot; Herrmann, Thomas; Chamulitrat, Walee (Biochemical and biophysical research communications, 2023)
Evidence from mice with global deletion of fatty-acid transport protein4 (FATP4) indicates its role on β-oxidation and triglycerides (TG) metabolism. We reported that plasma glycerol and free fatty acids (FA) were increased in liver-specific Fatp4 deficient (L-FATP4−/−) mice under dietary stress. We hypothesized that FATP4 may mediate hepatocellular TG lipolysis. Here, we demonstrated that L-FATP4−/− mice showed an increase in these blood lipids, liver TG, and subcutaneous fat weights. We therefore studied TG metabolism in response to oleate treatment in two experimental models using FATP4-knockout HepG2 (HepKO) cells and L-FATP4−/− hepatocytes. Both FATP4-deificient liver cells showed a significant decrease in β-oxidation products by ∼30-35% concomitant with marked upregulation of CD36, FATP2, and FATP5 as well as lipoprotein microsomal-triglyceride-transfer protein genes. By using 13C3D5-glycerol, HepKO cells displayed an increase in metabolically labelled TG species which were further increased with oleate treatment. This increase was concomitant with a step-wise elevation of TG in cells and supernatants as well as the secretion of cholesterol very low-density and high-density lipoproteins. Upon analyzing TG lipolytic enzymes, both mutant liver cells showed marked upregulated expression of hepatic lipase, while that of hormone-sensitive lipase and adipose-triglyceride lipase was downregulated. Lipolysis measured by extracellular glycerol and free FA was indeed increased in mutant cells, and this event was exacerbated by oleate treatment. Taken together, FATP4 deficiency in liver cells led to a metabolic shift from β-oxidation towards lipolysis-directed TG and lipoprotein secretion, which is in line with an association of FATP4 polymorphisms with blood lipids.